Psychological contract breach and job resources on work engagement - Norhizam, Natasha Ellyna; Mohd Anuar, Mohd Ashraff (Human Resource Management Academic Research Society, 2020)
In today's competitive job market, talent-competed companies are continuously focusing their efforts on enhancing the work engagement of employees, where it is a vital factor that could determine the success of the organization. However, when the employers or organization often promised the employees better rewards or promotion but ended up breaching the promises, this would cause disengagement among employees and loss of trust towards employers. It has been said that fulfiling job resources may help employees in stimulating their personal growth in the organization. This study aimed to determine the factors that influence the work engagement of employees. A random sample of 153 employees was selected from the private sector in Malaysia. The results of multiple regression analyses showed that only job resources boost work engagement. However, the authors did not find a relationship between psychological contract breaches and work engagement. The implications are discussed, and recommendations are presented.